Evaluation and Modification of Processes for Bioethanol Separation and Production - P Sitompul, Johnner; Widayat, Widayat; H. Soerawidjaja, Tatang (International Journal of Renewable Energy Development, 2012)
This paper concerns on process evaluation and modification for bioethanol separation and production by applying pinch technology. Further, the paper is also focused on obtaining a most energy-efficient process among several processes. Three basic process configurations of bioethanol separation and production were selected for this study. The three separations and production systems are Othmer process, Barbet process and a separation process that operates under vacuum condition. Basically, each process is combination of Danish Distilleries process with a separation system yielding 95% (v/v) bioethanol. The production capacity of the plant is estimated about 4 x 107 litre of bioethanol 95% (v/v) per year. The result of the studies shows that the most energy efficient process among the three processes evaluated is the Othmer process, followed by the Barbet process and the process involving vacuum operation. The evaluation also shows that further energy saving can be carried for Barbet and Othmer process configuration when ï„Tmin = 10oC for heat exchange possible.